Collaborative Information System to Find Efficient Routes Using Public Transport - Zanchett, Diego H. B.; P. Junior, Jurair R. de; Monteiro, André F.; Haddad, Diego B.; Assis, Laura S. de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
In recent years, the search to make cities smart often has been a strategy designed to mitigate problems generated by urban population growth. To improve the population’s quality of life and optimize the use of resources and infrastructure, applications in various fields have been developed. Public bus services are widely deployed in cities around the world because they provide costeffective public transportation. Most of the time the citizens are not provided information about the buses in real-time (location, route, etc). This paper address this lack of information on public bus services and presents ShareBus, an information system to improve urban mobility. The system architecture and its main functionalities are described. A preliminary implementation of the system is also presented which is evaluated through real tests. The system uses the idea of collaboration to obtain and maintain data, either from users or companies, keeping it as much as possible updated.